2017
DOI: 10.21608/ejabf.2017.3296
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight Relationship and Condition Factor of Some Fishes from the River Nile in Egypt with Special Reference to Four Tilapia Species

Abstract: This study has been carried out along the River Nile (river main stream, Rosetta and Damietta branches) in Egypt. Fish Samples of 21 species belonging to 11 families were collected mainly from the catch of three fishing gears and methods, Trammel net, Traps, and Long

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…This indicates that fishes grow almost symmetrically or isometrically in weight with length if its specific gravity remains constant which agree with the previous studies on these species in Egyptian waters (Ibrahim et al, 2007). Also, the result of this study agree with that of Shalloof and El-Far, (2017) who found in their study of length-weight relationship of some fishes from the River Nile that the value of (a) and (b) were 0.018 and 3.017 for O. niloticus and 0.019 and 2.997 for T. zillii.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that fishes grow almost symmetrically or isometrically in weight with length if its specific gravity remains constant which agree with the previous studies on these species in Egyptian waters (Ibrahim et al, 2007). Also, the result of this study agree with that of Shalloof and El-Far, (2017) who found in their study of length-weight relationship of some fishes from the River Nile that the value of (a) and (b) were 0.018 and 3.017 for O. niloticus and 0.019 and 2.997 for T. zillii.…”
Section: Discussionsupporting
confidence: 92%
“…Average condition factor for the species are close to these recorded for the same species. Shalloof and El-Far, (2017) reported in their study of condition factor of some fishes from the River Nile that the average K c for B. bayad, C. gariepinus, O. niloticusis, S. galilaeus and T. zillii were 0.954, 0.710, 1.919, 2.006 and 1.917, respectively which are comparable to that recorded in this study.…”
Section: Discussionsupporting
confidence: 86%
“…this type of growth indicates that the fish becomes relatively stouter or deeper-bodied as it increases in length [30]. This pattern was reported for O. niloticus by Mortuza and Al-Misned [31], Kembenya et al [32], Shalloof and El-Far [33], Cuadrado et al [34], Negaud [13], and Mohamed and Al-Wan [35] from various water bodies in the world. However, some authors reported negative allometric growth for this species in other waters, such as Novaes and Carvalho [36], Hassan and El-Kasheif [37], Khalifa [38], Teame et al [39], and Enawgaw and Lemma [40].…”
Section: Discussionsupporting
confidence: 61%
“…Research on the growth patterns or condition factors of the mudskipper has yet to be reported for Aceh Province. These parameters can be identified by measuring the length-weight relationship (LWRs) of fish in order to estimate the biomass of certain fish stocks and to manage fisheries resources (Karna et al 2018, Shalloof andEl-Far 2017) and as an indicator of fish condition (Froese 2006, Koutrakis andTsikliras 2003). Moreover, Muchlisin et al (2010) mentioned that growth patterns are critical parameters in fish farming because they can determine the results of cultivation.…”
Section: Introductionmentioning
confidence: 99%